Multicystic Dysplastic Kidney Disease: A Review: Multicystic Dysplastic Kidney - Akhavan Sepahi, Mohsen; Akhavan Sepahi, Mohammad Hossein; Akhavan Sepahi, Ali (Journal of Pediatric Nephrology, 2026)
The cystic kidney is one of the most common abnormalities detectable by ultrasound before and after birth and is also a cause of hydronephrosis; therefore, ultrasound is necessary for accurate diagnosis. Multicystic dysplastic kidney (MCDK) is a congenital disease in which the kidney is filled with multiple cysts and does not function properly. This article describes an article review of MCDK and new attention. This study aimed to increase awareness of the importance of diseases that cause kidney cysts, especially dysplastic multicystic kidney disease, to promote understanding of diagnostic methods before and after birth, and to investigate its cause.